FUNGSI MASJID SENDANG DUWUR SEBAGAI WUJUD AKULTURASI BUDAYA (The Roles Of Sendang Duwur Mosque As A Form Of Cultural Acculturation) - Novita Siswayanti (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Sendang Duwur Mosque built by Sunan Sendang Duwur not only plays as a place for worship, but also as cultural space to preserve religious tradition and acculturation between Islamic culture and pre-Islamic tradition. This study uses a qualitative descriptive approach to describe and to analyze the functions of Sendang Duwur mosque as manifestation of cultural acculturation. This mosque has conducted various religious activities that reflect cultural acculturation between pre-Islamic and Islamic culture. This mosque conducted a bancaan (eating together) and art performance terbang jidor, rebana with reading shalawat and barzanji with Javanese tune. These activities are to commemorate Islamic great days. There are various traditional foods served at the bancaan ceremony as a form of selametan or wilujengan (thanksgiving) which emphasize harmony among people within societies. This plays as a main lement of each ceremony in the system of Javanese religion. In addition, peoplevisiting mosque are for pilgrimage at Sendang Duwur tomb that aims to gain blessing and to follow the characters of Sunan. They hold selametan as well at the mosque for tasyakuran or praying to expect of safety from God.